Financial literacy: Factor influencing the level of financial literacy among college students (A study case: Kolej Poly-Tech Mara Kota Bharu) / Nor Fatimah Muhammad @ Harun - Muhammad @ Harun, Nor Fatimah (2016)
Understanding the factors that determine financial literacy and their effects can help policymakers or responsible parties and researchers to design and implement effective interventions for youth. Main focused of this research is to examine the factor that influences the level of financial literacy among college students. The study is used primary data by questionnaires and the sample consisted of 146 students and the target population of the study is from college Poly-Tech Mara Kota Bharu in Kelantan. SPSS software system is used for running the collected data. There are three independent variables such as financial attitude, financial knowledge and family influence whereby the dependent variable is the financial literacy. The results revealed that the family influence showed most significant positive relationship with the financial literacy, whereby the financial attitude and knowledge also significant but not strong as family influence. Finally, the limitation and recommendation are included to help further researchers to have a better finding of the result